2019
DOI: 10.1001/jamaoto.2019.0066
|View full text |Cite
|
Sign up to set email alerts
|

Association Between the Development of Pediatric Voice Disorders and Singing in Children’s Choir

Abstract: IMPORTANCE Pediatric vocal fold pathology is important because having a healthy voice free from disorders is crucial in a child's emotional and educational development. OBJECTIVE To determine whether there is an association between singing in a children's choir and the development of voice disorders. DESIGN, SETTING, AND PARTICIPANTS Prospective cohort study of children (aged 8 to 14 years) singers selected from local children's choirs and nonsingers selected from local schools evaluated at Clarós Otorhinolary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…We would like to clarify that both groups were evaluated in exactly the same way for LPR and reflux symptoms. However, owing to limitations caused by the uncertain nature of LPR diagnosis and no agreement across specialists on diagnostic criteria, this matter was just an additional observation in our study and was not included in the results (LPR was discounted from the voice disorders in our research) . Sataloff noted that there may be an association between singing training and the increased incidence of LPR owing to increased intra-abdominal pressure.…”
mentioning
confidence: 85%
“…We would like to clarify that both groups were evaluated in exactly the same way for LPR and reflux symptoms. However, owing to limitations caused by the uncertain nature of LPR diagnosis and no agreement across specialists on diagnostic criteria, this matter was just an additional observation in our study and was not included in the results (LPR was discounted from the voice disorders in our research) . Sataloff noted that there may be an association between singing training and the increased incidence of LPR owing to increased intra-abdominal pressure.…”
mentioning
confidence: 85%
“…To the Editor We thank Clarós et al for their study investigating the association between singing in a children’s choir and the development of voice disorders. The authors reported a significantly greater number of voice disorders in nonsingers compared with singers, thus emphasizing the importance of introducing conscientious voice care in nonsinging children.…”
mentioning
confidence: 99%
“…In addition, the authors remarked that instances of vocal trauma could result from shouting during team sports or playing with other children . They further postulated that this could be owing to the possibility that there are lower levels of vocal care awareness among nonsinging participants.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To the Editor Clarós et al should be complimented on the article “Association Between the Development of Pediatric Voice Disorders and Singing in Children’s Choir,” published online in March. The study was important.…”
mentioning
confidence: 99%